The newly found imagoes of Ochernova tshernovae (Kazlauskas, 1963) from China validating its position in the family (Ephemeroptera: Neoephemeridae) - Li, Meng-Yao; Deng, Mu-He; Zhou, Chang-Fa (Zootaxa, 2026)
Previously, the male imago of the mayfly Ochernova tshernovae (Kazlauskas, 1963) was not reported. The nymphs and adults of it found in northwestern China in 2025 not only show that this species has a vaster distribution than previously known but also demonstrate it is close to the European species Leucorhoenanthus maxima (Joly, 1871). Both of them share smaller posterolateral projections of abdominal terga in nymphs and smaller compound eyes in males than other genera. Biogeographically, this new finding illustrates that three neoephemerid genera of China (Ochernova, Potamanthellus, and Pulchephemera) are connected. Therefore, both its nymphs and adults are described in detail herein, and the observed biology of it is also presented.